Assessment of France Counter-terrorism Operation in Mali; Through the Lens of the Military Strategy. - Abass, Adam (Journal of Central and Eastern European African Studies, 2025)
Abstract: The Paper assessed France’s counter-terrorism operation in Mali and why it failed to bring about peace and stability in the country through a focused analysis of the counter-terrorism operation’s military strategy. The study seeks to understand why the decade-long operation, through its examination of the military strategy, fails to suppress the jihadist groups in the Sahelian country. The methodology employed in the paper includes using both qualitative and quantitative data. The findings of the paper reveal that the military strategy was characterised by an overwhelming use of military force, which only contained the threat and kept the conflict protracted, and also served as an incentive to join terror groups. It also finds out that the military strategy lacks a coherent military objective. This can be viewed from two perspectives: 1) its over-ambitious military objectives, and 2) the operation strategy’s inability to adapt to the evolving nature of the conflict; instead, the strategy is regarded as a “one-way plan”. The paper concluded by recommending that an overwhelming military-focused approach does not solve the terrorism problem; rather, it intensifies it and calls for the adaptation of alternative approaches.